V.D. Бonch-Bruyevich: «Professional» Revolutionary and One of the Founders of the Study of Religion in Soviet Union - D. D. Pyzikov (Концепт: философия, религия, культура, 2020)
The article is devoted to the first stage of the life and work of the scientist and researcher of minority religious groups, V.D. Bonch-Bruyevich (1873-1955). This choice is not accidental, since the beginning of the scientist’s creative and research journey is inextricably linked with his development as an individual and personality, his human qualities, desires and aspirations. Based on the methodology of intellectual history, the article attempts to reconstruct the history of the life and work of Bonch-Bruyevich. Thanks to the friendship with V.I. Lenin and active revolutionary activities, an important role was played by organizational work, as well as propaganda (from the early years of the 20th century, when he was an editor, publisher and employee of social democratic and Bolshevik newspapers and magazines). V.D. Bonch-Bruyevich entered the nomenklatura elite of the new state and in 1918 occupied the position of business manager of the Council of People’s Commissars. But unlike many activists of the revolutionary movement who before the revolution of 1917 perceived representatives of minority religious groups as «companions», he defended the believers’ rights to freedom of conscience before and after the revolution. At the same time, Bonch-Bruyevich never left his scientific activity and continued to practise until his last days, combining organizational and scientific work. His huge contribution to the study of religion in Russia and the formation of Soviet religious studies can not be overestimated. Studying the life and work of Bonch-Bruyevich, like other researchers of the Soviet period, is quite important, especially in the context of modern debates about Soviet humanities.